Potential Of Shallow Groundwater Utilisation Through Riverbank Filtration In Alor Pongsu - Leong, Chung Sum (2013)
The ever increasing demand for water in par with world population growth spurt has put an immense pressure on the conventional water supply system. Thus the distress for more water supplies has called for an alternative sustainable water resource. Riverbank Filtration (RBF) method, an existing but not fully explored area is now the subject of interest as the possible solution to all the water problems faced. As its potential needs assessment, few key areas requires detailed study and research. In preliminary studies, Earth Resistivity Image Profiling (RIP) is utilised to determine the existence of groundwater and suitable subsurface area for RBF setup. Boring and soil analysis were then carried out to verify the RIP results. Few important parameters of RBF method are looked into such as its quality, quantity, practicability and sustainability. Hydrochemical and microbiological tests were carried out to determine water quality while pumping test and environmental isotope tests were carried out to determine its quantity, practicability and sustainability. RBF had effectively removed most hazardous major ions in the mixture of river water and groundwater and most RBF water falls under class I-II quality. Total bacteria removal was also discovered at borehole 5 and 8. Whereas for pumping test of the aquifer, the results shows physical characteristics of a typical fast flowing sand layer while environmental isotope analysis shows degree of mixing up to 85 % of river water in groundwater. The minimum distance for an effective RBF is stipulated as more than 33 m in this research. Overall, RBF is a viable water treatment method and it holds a large potential in sustainable water resource development for Alor Pongsu.